Constraints associated with captivity alter craniomandibular integration in wild boar. Issue 2 (13th March 2021) - Neaux, Dimitri; Blanc, Barbara; Ortiz, Katia; Locatelli, Yann; Schafberg, Renate; Herrel, Anthony; Debat, Vincent; Cucchi, Thomas
Abstract: The domestication process is associated with substantial phenotypic changes through time. However, although morphological integration between biological structures is purported to have a major influence on the evolution of new morphologies, little attention has been paid to the influence of domestication on the magnitude of integration. Here, we assessed the influence of constraints associated with captivity, considered as one of the crucial first steps in the domestication process, on the integration of cranial and mandibular structures. We investigated the craniomandibular integration in Western European Sus scrofa using three‐dimensional (3D) landmark‐based geometric morphometrics. Our results suggest that captivity is associated with a lower level of integration between the cranium and the mandible. Plastic responses to captivity can thus affect the magnitude of integration of key functional structures. These findings underline the critical need to develop integration studies in the context of animal domestication to better understand the processes accountable for the set‐up of domestic phenotypes through time. Abstract : Morphological integration between biological structures is purported to have a major influence on the evolution of new morphologies. Here, we assessed the influence of constraints associated with captivity, considered as one of the crucial first steps of the domestication process, on the integration of cranial and mandibular structures in wild boar. Our results suggest that captivity can affect the magnitude of integration of these key functional structures.